Combining serum miR-144-3p and miR-652-3p as potential biomarkers for the early diagnosis and stratification of acute cellular rejection in heart transplantation patients. (3rd October 2022) - Perez-Carrillo, L; Gimenez-Escamilla, I; Snachez-Lazaro, I; Trivino, J C; Martinez-Dolz, L; Portoles, M; Tarazon, E; Rosello-Lleti, E
Abstract: Background: There is a dire need for specific, noninvasive biomarkers that can accurately and early detect cardiac acute cellular rejection (ACR). Previously, we described miR-144-3p as an excellent candidate to detect Grade ≥2R ACR. Purpose: Now, we investigated the combination of miR-144-3p with other differentially expressed serum miRNA that we previously described to improve diagnostic accuracy, mainly in mild rejection to avoid reaching severe stages. Methods: We selected miR-652-3p, miR-6747-3p and miR-221-3p from a preliminary RNA-seq study to be validated by RT-qPCR on 212 consecutive serum samples from transplantation recipients undergoing routine endomyocardial biopsies to subsequently combine them with miR-144-3p results and investigate their diagnostic capability. Results: We confirmed the miR-652-3p overexpression (p<0.0001) and its capability to discriminate between patients with and without ACR of any grade (p<0.0001), but not miR-6747-3p or miR-221-3p. The combined serum levels of miR-144-3p and miR-652-3p were significantly higher in patients with rejection regardless of posttransplantation time (p<0.0001). This combination resulted in a diagnostic efficacy for 1R (AUC=0.794) and ≥2R (AUC=0.892) (p<0.0001) that was superior to each biomarker alone. Furthermore, it was a strong independent predictor of ACR for 1R (odds ratio of 10.950, p<0.0001) and ≥2R (odds ratio of 14.289, p<0.01). Conclusions: We demonstrated that an appropriate combination of blood-based biomarkers can exhibit greater efficiency for cardiac rejection diagnosis. The combined detection of abnormal expression of miR-144-3p and miR-652-3p in the serum of ACR patients can improve the diagnostic sensitivity of rejection at the early stage and contribute to increasing the diagnostic accuracy, mainly in the lower rejection grades. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institute of Health Carlos III European Regional Development Fund (ERDF)